2023
DOI: 10.1111/jopy.12810
|View full text |Cite
|
Sign up to set email alerts
|

Personality, intelligence, and academic achievement: Charting their developmental interplay

Abstract: This manuscript has not been peer-reviewed and may be subject to change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 120 publications
0
9
0
Order By: Relevance
“…However, many of these studies either do not include time-varying controls for children's cognitive abilities, working memory, expectancies, or ability beliefs, or they consider only a specific subset of potentially relevant controls. This is concerning, given that all of these constructs have been hypothesized to influence children's math achievement (Bardach et al, 2023;Marsh et al, 2022;Weidinger et al, 2020;Zhang et al, 2023;Zimmerman, 2013). Critically, to the extent these variables are all causally important, the omission of these variables is likely to bias the relationship of measured variables between time points.…”
Section: Illusory Trait Hypothesismentioning
confidence: 99%
“…However, many of these studies either do not include time-varying controls for children's cognitive abilities, working memory, expectancies, or ability beliefs, or they consider only a specific subset of potentially relevant controls. This is concerning, given that all of these constructs have been hypothesized to influence children's math achievement (Bardach et al, 2023;Marsh et al, 2022;Weidinger et al, 2020;Zhang et al, 2023;Zimmerman, 2013). Critically, to the extent these variables are all causally important, the omission of these variables is likely to bias the relationship of measured variables between time points.…”
Section: Illusory Trait Hypothesismentioning
confidence: 99%
“…A large number of academic studies performed in the field of teaching and learning have confirmed the beneficial function that intelligence performs in students' academic life and their school-related accomplishments [38][39][40]. In the field of second/foreign language education, two contrasting viewpoints have emerged that attempt to explain the relationship between intelligence and language learning.…”
Section: Intelligence In Educationmentioning
confidence: 99%
“…Neuroticism has been found to be significantly negatively correlated with fluid intelligence (r = -.102; Anglim et al, 2022). Relationships between the other Big Five traits (Extraversion, Agreeableness, Conscientiousness) and intelligence have generally been found to be weaker and less consistent (e.g., Anglim et al, 2022;Bardach et al, 2022;Wolf & Ackerman, 2005).…”
Section: Big Five Personality Traits and Intelligence Test Performancementioning
confidence: 99%